The Emergence of Russian Liberalism - Berest, J. author. aut Link
VII, 271 p.
Keywords: A fresh perspective on the history of Russian liberalism through the life and work of Alexander Kunitsyn, a teacher and philosopher of natural law, whose academic and journalistic writings contributed to the dissemination of Western liberal thought among the Russian public.